A Comparative Study of the Outcomes of Surgically Versus Non‐Surgically Treated Spinal Disease in Patients With Multiple Myeloma: Northern Ireland's Experience - Amber McCalmont; Nagy Darwish; David Donaldson; Eiman Abdel Meguid (eJHaem)
ABSTRACT Background Multiple myeloma is a haematological malignancy which is characterised by the proliferation of cancerous plasma cells in the bone marrow. The role of spinal surgery in the management of myeloma is debatable. Therefore, this retrospective study aimed to compare the outcomes of treatment of patients with myeloma whose spinal disease was managed surgically and/or non‐surgically. Methods A total of 159 patients were reviewed retrospectively. To compare the outcomes of treatment in both cohorts, three outcome measures were selected, including back‐pain reduction, neurological status, and survival duration.  In addition, the extent and distribution of vertebral disease was assessed using MRI Whole Spine reports. Results There was no significant difference in the percentage of patients in each cohort reporting back‐pain pretreatment and at the two follow‐up periods (p > 0.05). Regarding neurological status, 23% of the surgical cohort improved, 53% remained stable and 7% deteriorated. In comparison, the non‐surgical cohort displayed no significant changes in neurological status post‐treatment. The mean duration of survival was significantly longer in the cohort who received surgery (77 vs. 24 months, p = 0.014). However, the mean age of diagnosis was significantly lower in this cohort (59 vs. 71 years, p < 0.001). T12 was the most commonly diseased vertebral level across both cohorts. At the time of diagnosis, the average number of diseased vertebrae per patient was 3.5 in the surgical cohort and 3.6 in the non‐surgical cohort. Conclusion This comparative study has shown that back pain alone should not be an indication for spinal surgery. However, surgical intervention may successfully prevent neurological deterioration. Although surgical intervention is associated with prolonged survival, this may be confounded by demographic variables, such as age. Importantly, most patients displayed multi‐level disease at the time of diagnosis. Trial Registration: The authors have confirmed clinical trial registration is not needed for this submission.